Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Motivasi Guru Terhadap Karakter Siswa di Gugus Sekolah Dasar Negeri (SDN) Lambada Klieng Kabupaten Aceh Besar - Wahyuni, Sri; Syarfuni, Syarfuni; Mukhlisuddin, Mukhlisuddin; Sari, Siti Mayang (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study was to determine the influence of the principal's leadership style and teacher motivation and student character in SD Negeri Cluster Lambada Klieng, Baitussalam District, Aceh Besar Regency. The type of research used is ex post facto with a quantitative approach. The study population was 117 teachers who taught at SD Cluster. The sampling technique uses random sampling, with a selected sample of 31 teachers from 9 elementary schools in the cluster. Data collection techniques use questionnaires, and the data is analyzed by simple regression calculations and multiple regression. The results showed that there was an influence of the principal's leadership style (X1) on the character of students (Y) in the Lambada Klieng Cluster, Baitussalam District, Aceh Besar Regency, with a percentage of 23%. There is an influence of teacher motivation (X2) on student character (Y) in SD Negeri Cluster Lambada Klieng, Baitussalam District, Aceh Besar Regency, with a percentage of 05.9%. There is an influence of the principal's leadership style (X1) and teacher motivation (X2) on the character of students (Y) in the Lambada Klieng Cluster, Baitussalam District, Aceh Besar Regency with a percentage of 23.4%.